2003
DOI: 10.1136/bmj.327.7423.1072
|View full text |Cite
|
Sign up to set email alerts
|

Deep vein thrombosis and air travel: record linkage study

Abstract: Objective To investigate the time relations between long haul air travel and venous thromboembolism. Design Record linkage study using the case crossover approach. Setting Western Australia. Participants 5408 patients admitted to hospital with venous thromboembolism and matched with data for arrivals of international flights during 1981-99. Results The risk of venous thromboembolism is increased for only two weeks after a long haul flight; 46 Australian citizens and 200 non-Australian citizens had an episode o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
76
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 18 publications
(21 reference statements)
12
76
1
5
Order By: Relevance
“…The results from studies suggest a 2-4-fold increased risk of thrombosis after air travel; [2][3][4] with a greater risk after longer flights than after shorter ones. 5,6 The mechanism of thrombus formation during air travel, however, is unclear.…”
Section: Introductionmentioning
confidence: 85%
“…The results from studies suggest a 2-4-fold increased risk of thrombosis after air travel; [2][3][4] with a greater risk after longer flights than after shorter ones. 5,6 The mechanism of thrombus formation during air travel, however, is unclear.…”
Section: Introductionmentioning
confidence: 85%
“…6 Fourth, travelling in trains for several hours may lead to immobility and predispose travellers to deep vein thrombosis. 7,8 Fifth, several pre-existing cardiovascular, respiratory diseases could exacerbate due to the strain involved during long-distance travel. 8 Since drugs play a major role in alleviating the signs and symptoms of most of the medical conditions that passengers encounter during their train journeys, inadequate knowledge about them could decrease their preparedness before a journey, decrease their ability to counter anticipated travel-related illnesses, and decrease reporting of adverse drug events.…”
Section: Introductionmentioning
confidence: 99%
“…This collection of symptoms, also called as 'travel-fatigue' , is also common in travellers in other modes of transportation. [6][7][8][9][10][11][12][13] Although, a majority of the participants actively sought help in case they encountered a medical problem while travelling, a substantial number did not want to do anything about it till their journey ended. This indicated that knowledge about the healthcare facilities provided by the Indian Railways and the drugs used to treat minor health problems encountered by travellers while travelling is sparse; hence, policy makers must take steps to generate more awareness about these two issues.…”
mentioning
confidence: 99%
“…A descriptive study on the rate of occurrence of fatal PE estimated the rate at 0.5 per million and 1.3 per million occurring among travelers taking flights of more than 3 hours and more than 8 hours, respectively (58) . The time frame that was reported for development VTE after prolonged flight was estimated at between 2 and 8 weeks (40) . In four prospective studies conducted on the development of VTE following travel, objective methods of evaluation of VTE were used prior to and after traveling (36,37,73,74) .…”
Section: Resultsmentioning
confidence: 99%